Cardiovascular safety during treatment with baricitinib in rheumatoid arthritis - Weinblatt, M; Taylor, P; Burmester, G; Witt, S; Saifan, C; Walls, C; Rooney, T; Chen, L; Takeuchi, T (Wiley, 2017)
Baricitinib (BARI) is an oral selective inhibitor of Janus kinase (JAK)1 and JAK2 approved in the EU for the treatment of active RA. Patients (pts) with RA have increased cardiovascular risk, including for arterial and venous occlusive events. This abstract examines the effects of BARI on cardiovascular events in RA.